2019
DOI: 10.2118/194503-pa
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Model Uncertainty in Probabilistic Decline-Curve Analysis for Unconventional-Oil-Production Forecasting

Abstract: Summary Decline-curve analysis (DCA) for unconventional plays requires a model that can capture the characteristics of different flow regimes. Thus, various models have been proposed. Traditionally, in probabilistic DCA, an analyst chooses a single model that is believed to best fit the data. However, several models might fit the data almost equally well, and the one that best fits the data might not best represent the flow characteristics. Therefore, uncertainty remains regarding which is the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Hong et al indicated that the least-squares estimation is a special case of MLE but a more-accurate data point will have more weight than a less-accurate data point using MLE, which improves the goodness of fitting. 21 Size of the historical data: the less the production data size, the higher the uncertainty. Production data quality: due to changes in the operating conditions with time to control BHP and multiple shut-ins, noise, outliers, and fluctuations of the historical production data appear and affect the fitting and therefore the reliability of the forecasting.…”
Section: Uncertainties Related To Decline Curve Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hong et al indicated that the least-squares estimation is a special case of MLE but a more-accurate data point will have more weight than a less-accurate data point using MLE, which improves the goodness of fitting. 21 Size of the historical data: the less the production data size, the higher the uncertainty. Production data quality: due to changes in the operating conditions with time to control BHP and multiple shut-ins, noise, outliers, and fluctuations of the historical production data appear and affect the fitting and therefore the reliability of the forecasting.…”
Section: Uncertainties Related To Decline Curve Studiesmentioning
confidence: 99%
“…In DCA, OLS is usually optimistic, while WLS is conservative, as shown in Figure . Hong et al indicated that the least-squares estimation is a special case of MLE but a more-accurate data point will have more weight than a less-accurate data point using MLE, which improves the goodness of fitting Size of the historical data: the less the production data size, the higher the uncertainty. Production data quality: due to changes in the operating conditions with time to control BHP and multiple shut-ins, noise, outliers, and fluctuations of the historical production data appear and affect the fitting and therefore the reliability of the forecasting. Flow regime variations through the production life: different transient flow regimes appear and could last for a very long time. There are many steps to decrease the degree of uncertainty related to DCA.…”
Section: Uncertainties Related To Decline Curve Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Gonzalez et al, 2012)) have attempted to identify a single ed as Pan CRM is this paper. Some researchers (e. Hong et al, 2019) have argued that selecting a single ed as Pan CRM is this paper. Some researchers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez et al, 2012) have attempted to identify a single "best" model among several DCA models. However, Hong et al (2019) have argued that selecting a single "best" model eliminates other potentially good models and exhibits overconfidence (i.e., trust the single model 100%), which can cause significant over/underestimates. Thus, their proposed approach incorporates multiple models by using Monte Carlo simulation to assess the probability of each model and consequently provides a probabilistic forecast of production.…”
Section: Introductionmentioning
confidence: 99%